Motor Cortex Stimulation Activates the Incertothalamic Pathway in an Animal Model of Spinal Cord Injury - Cha, Myeounghoon (2013)
We have shown previously that electrical stimulation of the motor cortex reduces spontaneous painlike behaviors in animals with spinal cord injury (SCI). Because SCI pain behaviors are associated with abnormal inhibition in the inhibitory nucleus zona incerta (ZI) and because inactivation of the ZI blocks motor cortex stimulation (MCS) effects, we hypothesized that the antinociceptive effects of MCS are due to enhanced inhibitory inputs from ZI to the posterior thalamus (Po)—an area heavily implicated in nociceptive processing. To test this hypothesis, we used a rodent model of SCI pain and performed in vivo extracellular electrophysiological recordings in single well-isolated neurons in anesthetized rats. We recorded spontaneous activity in ZI and Po from 48 rats before, during, and after MCS (50 μA, 50 Hz; 300-ms pulses). We found that MCS enhanced spontaneous activity in 35% of ZI neurons and suppressed spontaneous activity in 58% of Po neurons. The majority of MCS-enhanced ZI neurons (81%) were located in the ventrorateral subdivision of ZI—the area containing Po-projecting ZI neurons. In addition, we found that inactivation of ZI using muscimol (GABA(A) receptor agonist) blocked the effects of MCS in 73% of Po neurons. Although we cannot eliminate the possibility that muscimol spread to areas adjacent to ZI, these findings support our hypothesis and suggest that MCS produces antinociception by activating the incertothalamic pathway. PERSPECTIVE: This article describes a novel brain circuit that can be manipulated, in rats, to produce antinociception. These results have the potential to significantly impact the standard of care currently in place for the treatment of patients with intractable pain.